A bibliometric analysis of targeted therapy cardiotoxicity research in cancer patients (2004–2024) - Guoming Chen; Guang Chen; Huiping Zhou; Qingyi Yang; Yifan Shang; Rui Qin; Yingyue Hou; Cheng Zhang; Jiarui Lin; Xuan Ye; Ning Wang; Yibin Feng (Frontiers in Medicine, 2025)
BackgroundThe management of long-term cardiotoxicity has become increasingly challenging despite the growing utilization of targeted therapies to enhance progression-free and overall survival rates. Although there is a proliferation of literature on the incidence and mechanisms of cardiotoxicity induced by targeted therapies, no comprehensive analysis of the publication landscape has addressed the unmet medical needs in this area. This study aimed to characterize global research trends, map collaborative networks, and highlight unresolved issues in cardiotoxicity management to fill the gaps in this field and inform future research.MethodThis study conducted a bibliometric analysis of articles concerning targeted therapy-induced cardiotoxicity published between 2004 and 2024 from the Web of Science (WOS) database using VOSviewer and CiteSpace. A total of 1,054 publications from 71 countries/regions and 2,058 research institutions were examined.ResultThe number of publications has shown an average annual increase of 50 articles from 2004 to 2024. Key research topics in targeted therapy cardiotoxicity encompass breast cancer, heart failure, and drug delivery. The most cited publication is a guideline titled “Prevention and Monitoring of Cardiac Dysfunction in Survivors of Adult Cancers: American Society of Clinical Oncology Clinical Practice Guideline.” These results indicate a rising trend in research on tumor-targeted therapy cardiotoxicity over the past two decades. Recent research trends and future directions primarily focus on two key areas: the development of novel nanocarriers aims to enhance therapeutic efficacy while reducing cardiac toxicity, and the exploration of mechanisms underlying cardiac injury caused by targeted therapeutic drugs is crucial, along with the investigates drug interventions to counter these mechanisms or the application of alternative techniques for the prevention, alleviation, or treatment of cardiac injury.ConclusionThis study provides a comprehensive overview of targeted therapy-induced cardiotoxicity research from 2004 to 2024. By identifying key research priorities, this analysis addresses critical gaps in current knowledge. Future endeavors should prioritize translational innovations and multidisciplinary clinical frameworks to enhance therapeutic safety.